2021
DOI: 10.1002/ece3.7570
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence of daily activity in three ungulate species

Abstract: Daily activity in herbivores reflects a balance between finding food and safety. The safety‐in‐numbers theory predicts that living in higher population densities increases safety, which should affect this balance. High‐density populations are thus expected to show a more even distribution of activity—that is, spread—and higher activity levels across the day. We tested these predictions for three ungulate species; red deer ( Cervus elaphus ), roe deer ( Capreolus capreolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…What we did expect and found is that hunting ( β = − 0.34) and landscape abundance of red deer ( β = 0.41) explained patch utilization in opposing ways since this species negatively responds to hunting by human and because this is a social species that benefits from living in groups (Georgii 1981 ; Lone et al 2015 ). In line with our results, a companion study found that population size of red deer indeed positively explained variation in daily activity levels and spread (Ramirez et al 2021c ). Additionally, we expected that distance to forest edge would explain patch utilization as these areas are in the transition between forests and meadows and have therefore, a higher presence of herbaceous plants and a higher production of fresh tree leaves (Murcia 1995 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…What we did expect and found is that hunting ( β = − 0.34) and landscape abundance of red deer ( β = 0.41) explained patch utilization in opposing ways since this species negatively responds to hunting by human and because this is a social species that benefits from living in groups (Georgii 1981 ; Lone et al 2015 ). In line with our results, a companion study found that population size of red deer indeed positively explained variation in daily activity levels and spread (Ramirez et al 2021c ). Additionally, we expected that distance to forest edge would explain patch utilization as these areas are in the transition between forests and meadows and have therefore, a higher presence of herbaceous plants and a higher production of fresh tree leaves (Murcia 1995 ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have partially addressed how patch utilization by wildlife varies with top-down (Kuijper et al 2013 ; Shrader et al 2008 ), bottom-up forces (Rieucau et al 2009 ; Wei et al 2015 ), the landscape matrix (Rieucau et al 2007 ; Bubnicki et al 2019 ) and population size (China et al 2008 ; Ramirez et al 2021c ) but relatively few studies have analysed the relative importance of all these factors in combination. They show in agreement with the Optimal Foraging Theory that animals select patches with high quality food and with low predation risk, and their time in the patch is longer when being as a group (Brown 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship between vigilance and group size has been shown in many species (Isvaran, 2007 ) and is thought to arise from the benefits of shared vigilance in larger groups. This reduction allows animals to allocate more time to other key activities, such as foraging (Roberts, 1996 ), and to increase daily activity levels (Ramirez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Broekhuizen et al, 2016). Hunting levels in the Veluwe area can be up to 9.48 ungulates km −2 year −1 (Ramirez et al, 2021).…”
Section: Study Sitementioning
confidence: 99%